Controlling Structure with Injectable Biomaterials to Better Mimic Tissue Heterogeneity and Anisotropy. Issue 11 (5th May 2021) - Babu, Susan; Albertino, Filippo; Omidinia Anarkoli, Abdolrahman; De Laporte, Laura
Abstract: Tissue regeneration of sensitive tissues calls for injectable scaffolds, which are minimally invasive and offer minimal damage to the native tissues. However, most of these systems are inherently isotropic and do not mimic the complex hierarchically ordered nature of the native extracellular matrices. This review focuses on the different approaches developed in the past decade to bring in some form of anisotropy to the conventional injectable tissue regenerative matrices. These approaches include introduction of macroporosity, in vivo pattering to present biomolecules in a spatially and temporally controlled manner, availability of aligned domains by means of self‐assembly or oriented injectable components, and in vivo bioprinting to obtain structures with features of high resolution that resembles native tissues. Toward the end of the review, different techniques to produce building blocks for the fabrication of heterogeneous injectable scaffolds are discussed. The advantages and shortcomings of each approach are discussed in detail with ideas to improve the functionality and versatility of the building blocks. Abstract : The development of injectable scaffolds plays a pivotal role in the regeneration of sensitive tissues. Since most of these tissues have a complex structure and organization, conventional isotropic hydrogels by themselves cannot meet the requirements to mimic their anisotropic architectures. In this review, it is put together the major developments in low invasive material therapies from the past decade that incorporate heterogeneity and anisotropy in injectable systems with the aim to re‐establish tissue function.